(untitled) (Revista Iberoamericana de Estudios Municipales, 2025)
This present work analyzes three urban participatory urban planning processes in a mid size touristic city of Argentinean central Patagonia, Puerto Madryn, in the Chubut Province, that happened between 1996 and 2019. Through the reconstruction of its methodologies and teams, the description of its participatory forms, the main issues of its diagnosis and urban final models, we discuss the place of urban planning and social participation, the professional and ideological context and the models in the local sphere. We identify differences and similarities in the processes, in more professionalized and pragmatic scenarios that anyway turned to have equal outcomes, even when the participation was less massive and more mediated. Finally, we made a spatial analysis of the final urban models, what allowed us to confirm the similarities of the processes as well as the differences because of the crystallization of the interests of the main city landowners.